2017
DOI: 10.1371/journal.pone.0184384
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord homogenates from SOD1 familial amyotrophic lateral sclerosis induce SOD1 aggregation in living cells

Abstract: Mutant Cu/Zn superoxide dismutase (SOD1) can confer its misfolding on wild-type SOD1 in living cells; the propagation of misfolding can also be transmitted between cells in vitro. Recent studies identified fluorescently-tagged SOD1G85R as a promiscuous substrate that is highly prone to aggregate by a variety of templates, in vitro and in vivo. Here, we utilized several SOD1-GFP reporter proteins with G37R, G85R, or G93A mutations in SOD1. We observed that human spinal cord homogenates prepared from SOD1 famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…We also show that induced conversion of SOD1 species by TDP-43, in both HEK293FT cells and zebrafish, is specified by specific tryptophan residues in both proteins, militating for a direct proteinprotein interaction. For SOD1, the aggregation of SOD1 G85R -GFP (in cultured cells) and cross-seeding of wild-type SOD1 (in zebrafish) is dependent on surface-exposed SOD1 Trp32, similar to earlier studies of SOD1-SOD1 propagated misfolding (10,11,13,14,20). Cross-seeding of wild-type SOD1 by TDP-43 ∆ NLS and wild-type TDP-43, and SOD1 G85R -GFP aggregation, are all dependent on the natively solventexposed RRM1 Trp172, and the misfolding/aggregation-induced exposure of Trp68 by loss-of-structure of the TDP-43 N-terminal domain.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…We also show that induced conversion of SOD1 species by TDP-43, in both HEK293FT cells and zebrafish, is specified by specific tryptophan residues in both proteins, militating for a direct proteinprotein interaction. For SOD1, the aggregation of SOD1 G85R -GFP (in cultured cells) and cross-seeding of wild-type SOD1 (in zebrafish) is dependent on surface-exposed SOD1 Trp32, similar to earlier studies of SOD1-SOD1 propagated misfolding (10,11,13,14,20). Cross-seeding of wild-type SOD1 by TDP-43 ∆ NLS and wild-type TDP-43, and SOD1 G85R -GFP aggregation, are all dependent on the natively solventexposed RRM1 Trp172, and the misfolding/aggregation-induced exposure of Trp68 by loss-of-structure of the TDP-43 N-terminal domain.…”
Section: Discussionsupporting
confidence: 78%
“…Since SOD1 seeding and misfolding propagation is dependent on its single tryptophan residue, Trp32 (10,13,14), we speculated that TDP-43 might induce SOD1 misfolding and aggregation via one or more of its six Trp residues ( Fig 1A). Co-transfection of HEK293FT cells with SOD1 G85R -GFP reporter (13,20) and wild-type TDP-43 or nuclear localization signal mutant TDP-43 ∆ NLS revealed that SOD1 G85R -GFP aggregation was again strongly induced by these cytosolically mislocalizing and aggregating TDP-43 variants ( Fig 1B), supported by live-cell kinetic analysis ( Fig 1C). The induction of SOD1 G85R -GFP aggregation by wild-type TDP-43 or TDP-43 ∆NLS was confirmed independently by flow cytometry analysis showing a significant 3-fold increase in the induction of SOD1 G85R -GFP aggregation (Fig 1D and F).…”
Section: Interaction Between Tryptophan Residues Mediates the Intermomentioning
confidence: 66%
See 1 more Smart Citation
“…Further studies of the mechanism by which Trp 32 in SOD1 mediates the assembly of mutant SOD1 into larger aggregates may reveal potential avenues for therapy. Indeed, a recent study demonstrated that 5-fluoruridine, a compound that binds to SOD1 in a pocket that includes Trp 32, can attenuate the induced aggregation of SOD1:GFP in cultured cell models [73]. It may be of interest to generate transgenic mice that express mutant SOD1 with Trp 32 mutations to further explore the role of this residue in the macromolecular interactions that produce mutant SOD1 aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation of Trp 32 to Ser potently inhibited the ability of misfolded WT SOD1 to propagate between cells in culture [57,68,69]. Small molecules that bind near Trp 32 can block the seeding of mutant SOD1 aggregation in cell culture models [68,69,73]. In the present study, we used a combination of cell culture models and in vivo seeding models to examine the role of Trp 32 in modulating mutant SOD1 aggregation.…”
Section: Introductionmentioning
confidence: 99%